Identification of susceptibility modules and hub genes of osteoarthritis by WGCNA analysis - Wang, Yanchao; Zhou, Wenjun; Chen, Yan; He, Dong; Qin, Zhen; Wang, Zhao; Liu, Song; Zhou, Lei; Su, Jianwen; Zhang, Chi (Frontiers in Genetics, 2022)
Osteoarthritis (OA) is a major cause of pain, disability, and social burden in the elderly throughout the world. Although many studies focused on the progression of OA, its etiology remains unclear. Therefore, more biomarkers need to be explored to help early diagnosis, clinical outcome measurement and new therapeutic targets development. Our study aimed to retrieve the potential hub genes of osteoarthritis (OA) by weighted gene co-expression network analysis (WGCNA) and assess their clinical utility for predicting OA. Here, we integrated weighted gene co-expression network analysis to identify novel OA susceptibility modules and hub genes. In this study, we first selected 477 and 834 DEGs in GSE1919 and GSE55235 databases from the Gene Expression Omnibus (GEO) website. Genes with a (P-value<0.05 and a log2 fold change ≥ 1 were included in the analysis. Then, WGCNA was conducted to build a gene co-expression network, so as to filtered the strongest related modules and screened out 23 overlapping WGCNA-derived hub genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses elucidated that these hub genes were associated with cell adhesion molecules pathway, leukocyte activation and inflammatory response. What’s more, we conducted protein-protein interaction network in 23 hub genes, and the top 4 upregulated hub genes were sorted out (CD4, SELL, ITGB2 and CD52). Moreover, those top 4 hub genes showed good disease identification capacity by receiver operating characteristic (ROC) analysis (AUC=0.789) and nomogram model(C-index=0.76). These results were then verified in GSE51588 independent database. After that, a single-sample gene set enrichment (ssGSEA) analysis was performed to discover immune cell infiltration in OA. Finally, human primary synoviocytes and immunohistochemistry study of synovial tissues confirmed that those 4 hub genes were significantly up-regulated in OA groups compared with normal groups. We successfully constructed a co-expression network to explore OA-associated susceptibility modules and hub genes by WGCNA, and analyse their association with immune cell infiltration, which may contribute to the development of prediagnosis and targeted therapeutics for OA patients.